LABORATORIO BURBUJAS DE AMOR - Ortega Meneses, Luis (1992)
In the present case study, the shrimp larvae laboratory «Bubbles of Love», dedicated for providing larvae of this crustacean to shrimp companies, receives the proposal to supply a large company of the field, which would involve almost doubling its current production, but its installed capacity only allows it to increase by 25%. Therefore, if they decide to serve a new customer, they must find out how to finance the necessary investment for the expansion of facilities. The general conditions of the customer’s proposal, the background of the organization, the characteristics of the industry, the marketing of the product, the characteristics of the environment and different financing options are presented as well. The resolution of the case requires analyzing the information provided in order to determine the actual situation of the company and its financial capacity, the evaluation of different sources of financing as well, too.